LITERASI KEUANGAN SYARIAH DAN PENGARUHNYA TERHADAP EKONOMI YANG AKAN DATANG - Andreanto Indra Pratama; Fauzatul Laily Nisa (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This study aims to examine the level of Islamic financial literacy among the public and analyze its impact on future economic development. Islamic financial literacy encompasses an understanding of products, principles, and financial practices that comply with Shariah law, which is becoming increasingly relevant with the growth of the global Islamic finance industry. The research methodology employed is a quantitative approach through a survey involving 500 respondents from various demographic backgrounds. The research findings indicate that the level of Islamic financial literacy among the public is still relatively low, with knowledge limited to basic products such as savings and Islamic financing. However, there is a significant positive correlation between Islamic financial literacy and financial inclusion and economic stability. Improving Islamic financial literacy is expected to increase public participation in the Islamic financial system, strengthen economic stability, and promote more inclusive economic growth in the future. This study recommends more intensive education and socialization efforts from the government, financial institutions, and educational institutions to enhance Islamic financial literacy among the public.